Strategi KPU Kabupaten Bogor dalam Meningkatkan Partisipasi pada Pemilihan Umum Tahun 2019 - Triana Pertiwi; Siti Rahmawati (Yogyakarta State University, 2018)
Strategy of The General Election Commission (KPU) of Bogor Districts in Raising The Voters Participation on General Election 2019. The citizen's participation in politics that can be measurable is the citizen's behaviour in the election. The low level of participation is considered as an unfavourable sign that the government only serves the interest of some groups. The General Election Commission (KPU) as the election conventions plays a critical role as the facilitator between the candidates and the voters, they have to ensure the access of information and all the society's information necessities. Therefore, it needs to have the right strategy in raising the voters participation. The purpose of this research is to identify factors of the internal and external environments in raising the voters participation, to formulate the alternative strategies based on the internal and external factors and to define the right strategy that can be implemented by The General Election Commission (KPU) of Bogor districts. The research sample is chosen by using the nonprobability sampling method with a certain considerations (purposive sampling). The research methodology uses analysis of the IFE matrix, EFE matrix, IE matrix, SWOT and QSPM as the final decision the research resulting the main strategy that can be implemented, which is composing decisions the technique of election convention that is customized with Bogor district condition which based on the rules of regulations